Enteric and Intravenous Contrast Agents Used in Computed Tomography - Richard Burgner; James Rawson; Janet Munroe; Kandace Klein (Association of American Medical Colleges, 2014)
Abstract Recent estimates place the number of CT scans performed annually in the United States at approximately 70 million. Given the cost and radiation exposure, it is critical that CT is appropriate and performed with optimal technique. It is important to highlight the role of the radiologist as not just an interpreter of imaging, but as the expert specialist in the proper use of imaging. Accordingly, this tutorial will provide medical students a basic understanding of CT contrast agents, so that in the future they will be able consult effectively with radiologists and properly educate their patients. This presentation was created so that medical students can learn by reading and visualizing the application of different contrast material. All images provided in this tutorial were taken from our home institution except where indicated. This presentation is designed to be a self-tutorial. However, it is appropriate to also use as a stand-alone lecture. This presentation was originally given as a lecture to third- and fourth-year medical students as part of the daily afternoon lecture series for the introductory radiology clerkship. The presentation has now been incorporated into the radiology clerkship self-tutorial curriculum. This tutorial could be expanded into other modalities including contrast agents used in MRI, diagnostic radiography, etc. Being a general overview could be seen as a limitation of this resource. Each of this presentation's educational objectives could conceivably be expanded into its own tutorial for advanced radiology clerkships or resident training. Finally each institution's CT protocols are different. Thus, this tutorial could serve as a "base" in order to train students and residents the specific protocols used in their home institution.